TEACHERS' AND STUDENTS' VIEWS IN THE FIELD OF SCIENCE EDUCATION ABOUT PLAGIARISM - Nunes, Rose Cristina Alves (2024)
This study aims to identify the notions of teachers and students in the area of ​​Science Education regarding the topic of academic plagiarism and its interfaces. Data collection took place through an open questionnaire, with the participation of 15 researchers. Data processing was carried out based on the definition of three semantic categories: a) Academic plagiarism; b) Scientific methodology in research; and c) Disciplinary measures for plagiarism. The responses showed that the majority claim to have made improper copies in basic education. A certain group agrees with having made inappropriate duplications of texts during graduation, despite the majority having received guidance with information about plagiarism and its different formats. In their entirety, they define the concept of plagiarism, a significant number use anti-plagiarism tools, in addition to claiming to have received information on disciplinary measures to prevent plagiarism and guidance on possible sanctions in the postgraduate program to which they belong. It is important to highlight how much disclosure and guidance must be recommended and prioritized in the academic context, through different combat fronts, so that plagiarism is contained, before its possible occurrences.